Inducing endoplasmic reticulum stress in cancer cells using graphene oxide-based nanoparticles. Issue 10 (15th September 2020) - Pandey, Shalini; Nandi, Aditi; Basu, Sudipta; Ballav, Nirmalya
Abstract : Graphene oxide based self-assembled nanoparticles were developed to target the endoplasmic reticulum (ER) to induce ER stress in cancer cells. Abstract : The endoplasmic reticulum is one of the vital organelles primarily involved in protein synthesis, folding, and transport and lipid biosynthesis. However, in cancer cells its functions are dysregulated leading to ER stress. ER stress is now found to be closely associated with hallmarks of cancer and has subsequently emerged as an alluring target in cancer therapy. However, specific targeting of the ER in a cancer cell milieu remains a challenge. To address this, in this report we have engineered ER-targeted self-assembled 3D spherical graphene oxide nanoparticles (ER-GO-NPs) encompassing dual ER stress inducers, doxorubicin and cisplatin. DLS, FESEM and AFM techniques revealed that the nanoparticles were spherical in shape with a sub 200 nm diameter. Confocal microscopy confirmed the specific homing of these ER-GO-NPs into the subcellular ER within 3 h. A combination of gel electrophoresis, confocal microscopy and flow cytometry studies revealed that these ER-GO-NPs induced ER stress mediated apoptosis in HeLa cells. Interestingly, the nanoparticles also activated autophagy which was inhibited through the cocktail treatment with ER-GO-NPs and chloroquine (CQ). At the same time these ER-GO-NPs were found to be efficient in prompting ER stress associated apoptosis in breast, lung and drug resistant triple negative breast cancer cell lines as well. We envision that these ER specific self-assembled graphene oxide nanoparticles can serve as a platform to exploit ER stress and its associated unfolded protein response (UPR) as a target resulting in promising therapeutic outcomes in cancer therapy.